The Role of Strategic Leadership in Driving Effective School Reform Initiatives - Fahmi, Ansari; Nasution, Inom (Universitas Negeri Malang, 2024)
Abstract: This research aims to examine the role of strategic leadership in facilitating school reform and improving educational outcomes. It investigates how effective leadership can contribute to the success of educational change initiatives and their impact on student performance. This research uses a qualitative method approach. These findings suggest that strategic leaders play a critical role in driving educational change by fostering a culture of innovation, collaboration, and continuous improvement. The results also show that strategic leadership can improve the quality of education in the school environment, including increased academic achievement and better student engagement. The strategic leadership carried out by the school principal to realize change is to provide opportunities for teachers to provide educational innovation and assist teachers in facilitating workshop training and mentoring activities. In this way, school principals can help improve the quality of education and increase teachers' awareness of their role in the teaching and learning process, as well as encourage positive change for schools. Keywords: Strategic Leadership; School Reform